A Liquid Band-Aid with Mesenchymal Stem Cell-derived Exosomes for Wound Healing in Mice - Zhang, Wei-Yuan; Meng, Tian-Jiao; Hu, Jia; Wen, Li; Du, Li; Cheng, Xiao-Chen; Wang, Li-Sheng; Xiao, Feng-Jun; Lu, Yu-Xin (Current Pharmaceutical Biotechnology, 2025)
Introduction/ObjectiveThis study aimed to examine the effect of a human umbilical cord mesenchymal stem cell-derived exosome (hUC-MSC-Exo) liquid band-aid on wound healing in mice.MethodshUC-MSC-Exos were prepared from the supernatant via ion exchange chromatography. The composition ratio of the chitosan liquid band-aid was optimized to form a film and encapsulate hUC-MSC-Exo. The biological effects of chitosan exosome liquid band-aid on human umbilical vein endothelial cells (HUVECs) were observed, and its anti-bacterial properties were tested. BALB/c mice with back skin injury were randomly divided into chitosan exosome liquid band-aid group (CS-Exo), chitosan liquid band-aid group (CS), and normal saline control group (Con), and wound healing was evaluated post-treatment. Skin tissue samples post-treatment were collected for H&E staining.ResultsThe hUC-MSC-Exo was prepared and characterized. The optimum conditions for film formation were 1% chitosan solution and 15% poloxamer 407/poloxamer 188 (pH 5.0 7.0). The chitosan exosome liquid band-aid promoted HUVEC proliferation and migration and markedly inhibited Escherichia coli and Staphylococcus aureus growth in vitro. In vivo, the wound healing rate in the CS-Exo group was higher than that in the Con and CS groups. Fourteen days post-treatment, the wounds completely healed, and hair grew normally, which was consistent with H&E results. Mouse weights in each group did not change significantly after administration, indicating that the chitosan exosome liquid band-aid had no obvious toxic side effects.ConclusionLocal chitosan exosome liquid band-aid application can promote wound healing in mice, and the mechanism could be related to hUC-MSC-Exo-induced vascular endothelial cell proliferation and migration.
Keywords: chitosan